Keefektifan Pendekatan Asesmen Kinerja dan Kemampuan Berpikir Kreatif Peserta Didik terhadap Hasil Belajar Matematika Kelas VIII SMP Negeri 1 Blahbatuh - Ni Wayan Sunita; I Wayan Eka Mahendra; Ni Wayan Darmayani (FPMIPA IKIP PGRI Bali, 2018)
The purpose of this research is to know the effect of performance assessment approach and the the ability to think creatively to the study result of mathematics student class VIII at SMP Negeri 1 Blahbatuh, and to know which assesssment approach is better used in obtaining better result of mathematics. In the implementation, in the experimental group is given treatment in the form of performance assessment and control group is given treatment in the form of conventional assessment. This research is categorized quasi experiment with the design of Treatment by Level.The population in this research is all the students of class VIII at SMP Negeri 1 Blahbatuh which consist of 346 people.The study sample involved as many as 78 people in the experimental class and 77 people in the control class. Samples were taken randomly with multistage random sampling technique. The instrument used in this research is the test for result of mathematic and the ability to think creatively. In this research data analysis using analysis of variance test (ANAVA) Two Path and further test that is Tukey test. The result of this study show there is the differences result of mathematics between students who were assessed using performance assessment with students assessed using conventional assessment. Further interaction between the assessment form and the level of the ability to think creatively toward the the result of mathematic. For learners who have high creative thinking ability more suitable given the performance assessment, while learners who have low creative thinking ability more suitable given conventional assessment.